Analysis of Pollutant Emission Characteristics of Marine Diesel Engine Using Chemical Kinetics under the Background of Energy Shortage. (June 2020) - Sun, Changfei; Hui, Jie
Abstract: The study aims to reduce the environmental pollutants produced in the ship transportation in the environment of energy shortage, and realize the comprehensive development of energy saving and emission reduction. Based on the theoretical basis of chemical kinetics, a new type of NOx emission generation model of marine diesel engine was proposed according to the traditional HB model. Second, the combustion chemical kinetics of sulfide was described, on which the sulfide generation and emission model of marine diesel engine was proposed. Third, the characteristics of NO, N2 O and SO2 were analyzed according to the emission model of NOx and sulfide generation in marine diesel engine. The results showed that when the crankshaft angle was 230° and 250°CA, the content of NO and N2 O in the exhaust pipe of diesel engine had an obvious peak. The content of NO and N2 O in the cylinder and exhaust pipe of diesel engine increased at the beginning. As the crankshaft angle increased, the content of both decreased gradually, and the trend of change in the cylinder was slower than that in the exhaust pipe. The SO2 content in the diesel cylinder kept stable after a small increase until it disappeared. The SO2 content in the exhaust pipe first increased and then decreased. When the crankshaft angle was 230°CA, the SO2 content in the exhaust pipe of the diesel engine had an obvious peak. The emission characteristics of nitrogen oxide and sulfide were consistent with the correct change trend, which conformed to the theoretical mechanism. In a word, the study provides a practical basis for energy conservation and emission reduction, development of low-carbon economy, and efficient use of energy.